Shaken brain : the science, care, and treatment of concussion - Sandel, Elizabeth (Harvard University Press, 2020)
"Sports concussions make headlines, but you don't have to be an NFL star to suffer traumatic brain injury. In Shaken Brain, Elizabeth Sandel, MD, shares stories and research from her decades treating and studying brain injuries. She explains what concussions do to our bodies, how to avoid them, and how to recover"--